Axial and Lateral Small Strain Measurement of Soils in Compression Test using Local Deformation Transducer - Nawir, Hasbullah; Apoji, Dayu; Ekawita, Riska; Khairurrijal, Khairurrijal (Journal of Engineering and Technological Sciences, 2018)
This paper presents the development of a method using local deformation transducers (LDTs) to locally and sensitively measure small axial and lateral strains in soil in a compression test. A local strain measurement system comprising of axial and lateral LDTs was developed referring to the original LDT system and the cantilever LDT system, respectively. The LDTs were calibrated both in air and under water. Their insensitivity to pressurized water was confirmed. The calibration factors for the axial and lateral LDTs were found to be 1.695 mm/volt and 1.001 mm/volt, respectively. The performance in terms of repeatability and stability of the LDT system was evaluated. The repeatability test showed that the average standard deviation of the lateral LDT was 0.015 volt, while the stability test showed that the average standard error of the axial and lateral LDT were 3.13 Ã 10-5 volt and 2.65 Ã 10-5 volt, respectively. Unconfined compression tests were conducted on three reconstituted clay samples to examine the proposed axial and lateral LDT system. The stress-strain relationship indicates a nonlinear relationship between the axial and lateral strain of soil instead of the conventionally assumed constant relationship. The results demonstrate this nonlinear behavior even at small strain levels, which were successfully measured using a domestically built axial and lateral LDT system.